Safety perspectives of high-school students in western China: rural-urban and gender comparison. Issue 3 (3rd April 2021) - Qi, Xinjian; Routray, Jayant K.; Ahmad, Mokbul Morshed
ABSTRACT: School safety within and outside the schools is a priority for school heads, teacher education administrators and the governments around the globe. In China, despite several policy instruments, rules and regulations, school safety is often questioned and highlighted in the print and TV media. There is a need to address the issues associated with school safety and provide improved educational environments for male and female students in rural and urban areas. This paper uses 12 indicators to assess the safety status in schools in a remote province of Gansu, China and provide a comparative perspective between urban and rural schools and along gender lines.